Szkoła Mateusza czy szkoła Jezusa? - Wróbel, Mirosław Stanisław (Verbum vitae, 2002)
Recenzja: Samuel Byrskog, Jesus the Only Teacher. Didactic Authority and Transmission in Ancient Israel, Ancient Judaism and The Matthean Community, Stockholm 1994, ss. 485.